The attractiveness of FX housing loans for housholds in view of supervisory actions in selected EU countries - Marta Świerczyńska; Mariola Węglińska (e-Finanse: Financial Internet Quarterly, 2017)
The article relates to the attractiveness of FX housing loans for households which led to over increase in EU countries. Results of comparative analysis conducted for Poland, Austria, Romania and Hungary indicates that actions taken by the supervisory bodies dedicated to demand indicators influence credit increase limitation in different ways. Non-standard actions taken seem to be most effective. Nevertheless, looking at the Hungarian caseit brings high costs to the economy.
Keywords: D14; E58; G21; G28; 330; FX loans; housing loans; risk; supervisory actions; customers; households